The effect of vacuum frying on starch gelatinization and its in vitro digestibility in starch–gluten matrices. (15th April 2016) - Contardo, Ingrid; Parada, Javier; Leiva, Angel; Bouchon, Pedro
Highlights: Starch gelatinization was notably reduced in vacuum fried matrices. This produced a weak structure that facilitated surface oil removal. Rapid available glucose and unavailable glucose were comparable to raw dough. Atmospheric fried samples had a big decrease of unavailable glucose. Potential of vacuum processing to control structure and starch digestibility. Abstract: Starch digestibility in a food matrix depends on processing conditions that may affect its physical state and microstructure. Starch gelatinization is one critical change that takes place during frying which could be affected during low-pressure processing. This study assessed the effect of vacuum frying on starch gelatinization and its in vitro digestibility. Laminated dough was made of a reconstituted blend of wheat starch (88% d.b.) and gluten (12% d.b.). Samples were fried under vacuum (6.5 kPa, T water-boiling-point  = 38 °C) or atmospheric conditions up to bubble-end point, maintaining a thermal driving force of 70 °C ( T oil  −  T water-boiling-point  = 70 °C). Vacuum fried samples showed less starch gelatinization (28%), less rapidly available glucose (27%), and more unavailable glucose (70%) than their atmospheric counterparts (which presented 99% starch gelatinization, 40% rapidly available glucose, and 46% unavailable glucose ), and the values were close to those of raw dough. These results show how vacuum processing may be used to control the degree of starch gelatinization and related digestibility.